Real-World Visual Outcomes and Rotational Stability of a Monofocal Toric Intraocular Lens - LaHood B; Peterson RC (Clinical Ophthalmology)
Ben LaHood,1 Rachael C Peterson2 1Adelaide Eye and Laser Centre, Adelaide, South Australia, Australia; 2Alcon Research, Fort Worth, TX, USACorrespondence: Ben LaHood, Adelaide Eye and Laser Centre, 215 Greenhill Road, Adelaide, South Australia, 5063, Australia, Tel +61 451545323, Email ben@drbenlahood.comPurpose: To assess the real-world distance and intermediate visual outcomes, rotational stability, and adverse events (AEs) of patients implanted with a Clareon aspheric monofocal toric intraocular lens (IOL) preloaded in the AutonoMe delivery system (Alcon, USA; models CNA0T2 to CNA0T6) up to one-month postoperative.Methods: Surgical charts from January 2021 to October 2023 were reviewed for adult patients (≥ 18 years) who previously received a CNA0T2 to CNA0T6 (T2 to T6) IOL during uneventful cataract surgery and were targeted for emmetropia/first minus. Overall, charts from 193 eyes of 121 patients were screened, with 161 eyes of 107 patients included in the study. Data were collected from preoperative, and postoperative records up to approximately one-month (4– 5 weeks), and included monocular corrected distance visual acuity (CDVA), uncorrected and distance-corrected intermediate visual acuity (UIVA and DCIVA), residual astigmatism, and absolute IOL rotation (measured from the axis position at the end of surgery up to one-month).Results: For the full cohort (T2 to T6 IOLs, n=161 eyes), CDVA was − 0.01 ± 0.07 logMAR at one-month. Monocular UIVA was 0.22 ± 0.14 logMAR, DCIVA was 0.24 ± 0.12 logMAR, and absolute IOL rotation was 1.02 ± 1.21°. Residual astigmatism was very low (< 0.01D) and consistently low across T2 to T6 IOLs. A T3 to T6 sub-analysis (n=64 eyes) found CDVA of − 0.01 ± 0.07 logMAR, UIVA of 0.20 ± 0.14 logMAR, DCIVA of 0.23 ± 0.13 logMAR, and absolute rotation of 1.08 ± 1.26°. For all eyes, 1 serious ocular AE, cystoid macular edema, was identified. No serious non-ocular AEs, device deficiencies, or posterior capsular opacification were observed.Conclusion: The Clareon aspheric monofocal toric IOL showed excellent improvement in distance visual acuity and treatment of astigmatism, with functional intermediate visual acuity and minimal rotation.Keywords: Clareon toric, intermediate vision, residual astigmatism, rotational stability